Modeling and experimental validation to estimate the energy balance for a poultry house with misting cooling (2011)
The aim of this study was to develop and validate a simplified steady state mathematical model to predict temperature distribution in a commercial poultry house equipped with a negative pressure ventilation system and internal misting. The model was validated with data obtained experimentally during the summer. For external temperature conditions of 26, 27, and 29 °C, the best combinations of energy generated by misting (qmisting), ventilation rate (V), global heat loss coefficient for the roof (Ut), and global heat loss coefficient for the wall (Upar) were encountered to maintain the majority of the installation with temperatures within the optimal thermal comfort range for the birds (24 to 29 °C).